Analytical Case Study of the SUCCESS School Project in Four Mandals of Visakhapatnam District, Andhra Pradesh - Terapalli, Prakash; Raju, R. Satya Bala Ratna; Prasad, V. Joshua Jaya (INDIAN EDUCATIONAL REVIEW, 2016)
In the global market, a rapid development is seen in the field of Science and Technology and innovation. Now days, students have more inclination to do work in the global village. So it is important to equip the students with required abilities for the future needs; education plays a key role. For the proper foundation of a student, a teacher should take care about the education of the child from the root level. With the vision to increase global opportunities for the budding rural youth, Government of Andhra Pradesh has launched an excellent project ‘SUCCESS’ in 2006. It is implemented in the selected schools. But the outcome from the project not equips the student with the global standards. Hence, we did the survey to know the resons by considering a sample of 15 schools in 4 mandals of Visakhapatnam. For the analysis, five parameters such as Infrastructure facilities, Human Resource, Financial support, Establishment of Laboratories and Furniture and Teaching Learning Methods, are considered. In each parameter sub parameters are considered for the survey and corresponding evaluation forms are prepared for the survey. However, result points out the improvement needed in the implementation of the project.